Effect of the Addition of Red Dragon Fruit (Hylocereus polyrhizus) Extract on the Characteristics of Belimbing Wuluh (Averrhoa bilimbi, L.) Syrup - Yenrina, Rina; Sylvi, Diana; Devi, Retno Gusti (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
This study aims to determine the effect of the addition of red dragon fruit juice on the characteristics and organoleptics of belimbing wuluh syrup. The experimental design used in this study was a completely randomized design (CRD) with five treatments and three replications. The treatment carried out in the study was the addition of red dragon fruit juice at concentrations of 0%, 5%, 10, 15%, and 20%. The results showed that the addition of red dragon fruit juice had a significant effect on physical tests (color), chemical tests (pH, total sugar content, vitamin C, total acid, antioxidant activity, betacyanin levels), and organoleptic tests (color and taste). and did not have a significant effect on the organoleptic test (aroma). The best treatment based on physical, chemical, microbiological, and organoleptic properties was the addition of red dragon fruit juice with a concentration of 20%, with color test results of 17.87Â°H, pH (3.67), total sugar content (73.99%), vitamin C (16.19 mg/100g), total acid (1.11%), antioxidant activity (44.65%), betacyanin content (1.63%), total plate number (2.46 102 CFU/g), and organoleptic analysis of color 4.20 (like), aroma 3.55 (like), and taste 3.85 (like).